Pengembangan Instrumen Evaluasi IPA Berbasis Platform Wordwall Untuk Siswa Kelas VI SDN 7 Manukaya Pada Materi Tata - Ulan Dari, Ni Komang Ayu; Numertayasa, I Wayan; Pradnyana, Putu Beny (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2025)
This study aims to: (1) Determine the needs of teachers in implementing a science learning evaluation instrument based on the Wordwall educational game on the solar system material in class VI of SD N 7 Manukaya; (2) Determine the prototype of the Wordwall-based evaluation instrument that was developed; and (3) Determine the validity of the instrument. This study uses the Research and Development (R&D) method with the following stages: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, and (5) revision. Data collection techniques include closed questionnaires, structured interviews, observation, and documentation, with the research subjects being teachers and students of SD N 7 Manukaya and the object being the learning evaluation instrument. Validation was carried out by three experts. The results of the study show that: (1) Teachers really need a web-based evaluation instrument because written evaluations tend to be boring for students; (2) The prototype was developed in the form of an interactive quiz with 25 questions displayed through an educational game on the Wordwall platform; (3) The validation results show an average score of 86, which is included in the valid category. Thus, this instrument is worthy of being used as an alternative to interesting and enjoyable learning evaluation.